Crop Water Deficit Index at Phenophases and Yield of Kharif Crops in Gujarat - Sahu, D D; Sastry, P S.N (Annals of Arid Zone, 2016)
Aridity index is derived in relation with individual growth phases of Kharif crops and designated as crop water deficit index (CWDI). Weekly indices were cumulated from sowing to maturity to get 'seasonal' CWDI. Yield and phenophasic CWDI were found to be negatively correlated while the CWDI during flowering and grainfilling stages of crops were significantly correlated with yield. The impact of seasonal and phenophasic crop water deficit is reflected in the crop productivity and its variability at different stations in Gujarat.